2020
DOI: 10.1002/slct.202000148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flower‐Like and Spherical Nanostructured MoS2 on the Adsorption Properties of Cr(VI) Ions

Abstract: MoS2 nanostructures with different morphologies were synthesized using a simple in‐situ hydrothermal process by different surfactants like hexadecyl trimethyl ammonium bromide (CTAB) and polyvinyl pyrrolidone (PVP), and the effect of morphologies on the adsorption property for Cr(VI) were investigated. It can be found that flower‐like and spherical MoS2 nanostructures were synthesized and their morphologies largely effected the adsorption performance toward Cr(VI) ions. Flower‐like MoS2 exhibited the surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It is reported that 1T MoS 2 exhibited the high adsorption capacity (200.3 mg/g), compared to 2H MoS 2 (70.7 mg/g) and M MoS 2 (82.8 mg/g, Figure A) . Sun et al reported that the maximum sorption capacity of Cr­(VI) on pristine 2D MoS 2 via a facile one-step hydrothermal method was 84.03 mg/g, which was slightly higher than the flowerlike nanostructures MoS 2 through a surfactant-assisted hydrothermal method (66.1 mg/g) . In order to increase the adsorption performance and redox capacity, various MoS 2 -based composites were widely synthesized in recent years.…”
Section: Environmental Applicationmentioning
confidence: 96%
See 1 more Smart Citation
“…It is reported that 1T MoS 2 exhibited the high adsorption capacity (200.3 mg/g), compared to 2H MoS 2 (70.7 mg/g) and M MoS 2 (82.8 mg/g, Figure A) . Sun et al reported that the maximum sorption capacity of Cr­(VI) on pristine 2D MoS 2 via a facile one-step hydrothermal method was 84.03 mg/g, which was slightly higher than the flowerlike nanostructures MoS 2 through a surfactant-assisted hydrothermal method (66.1 mg/g) . In order to increase the adsorption performance and redox capacity, various MoS 2 -based composites were widely synthesized in recent years.…”
Section: Environmental Applicationmentioning
confidence: 96%
“…210 Sun et al reported that the maximum sorption capacity of Cr(VI) on pristine 2D MoS 2 via a facile one-step hydrothermal method was 84.03 mg/g, 213 which was slightly higher than the flowerlike nanostructures MoS 2 through a surfactant-assisted hydrothermal method (66.1 mg/g). 214 In order to increase the adsorption performance and redox capacity, various MoS 2based composites were widely synthesized in recent years. For instance, Yang et al reported that the maximum sorption capacities of Cr(VI) on MoS 2 @Fe 3 O 4 composites (290.2 mg/g at pH 5.0, T = 298 K, Figure 5B) 208 was significantly higher than those of the other MoS 2 -based composites such as MoS 2 / CTAB (79.4 mg/g), 212 MoS 2 /rGO(80.8 mg/g), 211 LDHs@ MoS 2 (76.3 mg/g at pH 5.0), 215 chitosan-modified/MoS 2 (158 mg/g at pH 5.0).…”
Section: Environmental Applicationmentioning
confidence: 99%